What's the Point of Using Computers? : The Development of Young People's Computer Expertise in the Home - FACER, KERI and SUTHERLAND, ROSAMUND and FURLONG, RUTH and FURLONG, JOHN (New Media & Society, 2001)
Despite the column inches and policy statements dedicated to arguing that young people need to use computers, very little is known about the reasons why young people themselves might value and acquire computer expertise. Drawing on a survey of 855 children and 16 detailed case studies of children's use of computers at home this article explores the influence of software design, family discourses, peer group culture and gender identity on children's perception of the potential uses and benefits of ICT expertise. The article goes on to argue that young people value and acquire computer expertise primarily in order to achieve practical objectives and in relation to the construction of (gendered) peer group identities. Given these findings the article questions the continued emphasis in educational policy on the acquisition of decontextualized information and communications technology (ICT) `skills' within a rationale of future relevance to the workplace.
https://katalog.adlr.link/Record/ai-49-aHR0cDovL2R4LmRvaS5vcmcvMTAuMTE3Ny8xNDYxNDQ0ODAxMDAzMDAyMDA0